Nursing competencies in geriatric rehabilitation and palliative care team - Šaponjski Jelena (Association of Nurses Technicians and Midwives, 2015)
Rehabilitation is a process which enables persons with physiological or anatomical abnormalities to achieve their optimal physical, psychological, social, vocational and avocational status. It means more than simple physical restoration, compensation of the loss of a function or adapting to the physical loss - appearance. Persons with limited mobility have lost their limb function or mobility of a body part. Depending on the kind of functional loss, these people may have a problem in handling objects or they may need assistance for some other functions. When curative medicine is not helping any more, patients are included into palliative care. Palliative care is an approach that improves the quality of life of patients and their families facing the problems associated with life-threatening disease, through the prevention and relief of suffering, by means of early identification and impeccable assessment and treatment of pain and other problems, physical, psychosocial and spiritual. Nurses play a very important role in an interdisciplinary team since they provide help, support and encouragement for patients in direct contact with them and their family; moreover, they make a valuable contribution to the rest of the team since they are present 24 hours a day. Due to the difficult and complex situation, they are required to comply with all ethical principles, especially principles of confidence, doing good and avoiding evil. They foster a professional relationship with seriously ill patients, showing understanding for their needs. At the same time, they help the rest of the team to offer better and more efficient health services by keeping medical records. They do their best to relieve total pain and total suffering.